Analysis of Factors Affecting the Success of Pulmonary TB Treatment in the Working Area of Puskesmas Sukaramai, Pakpak Bharat District - Krisna Dona Br Sembiring; Nur'aini Nur'aini; Aida Fitria (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Tuberculosis disease is still a global problem at this time, the WHO (World Health Organization) report in 2023, there were 9.6 million people in the world suffering from pulmonary tuberculosis and 1.5 million of them died. While the number of cases of pulmonary TB at the Sukaramai Health Center in 2023 was 321 total cases and 43 people recovered. The purpose of the study was to analyze the factors that influence the success of Pulmonary TB treatment in the Sukaramai Puskesmas Working Area, Royal District, Pakpak Bharat Regency. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all TB patients who sought treatment at the Sukaramai Health Center, namely 101 patients, all of whom were sampled using the total population technique. Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression. The results of logistic regression research show that there is an influence of knowledge p = 0.000, family motivation p = 0.001 adherence to taking medicine p = 0.003 and side effects of drugs p = 0.010. While the dominant factor that influences the success of Lung TB treatment is knowledge p = 0.000 with an Exp(B) value of 60.141, meaning that knowledge has 60 times the risk compared to other variables. The conclusion of this study is that there is an influence of knowledge, family motivation, adherence to taking medication and side effects of drugs on the successful treatment of Pulmonary TB in the Working Area of ??the Sukaramai Health Center, Royal District, Pakpak Bharat Regency and variables that do not affect the distance of health services. It is recommended for patients with pulmonary tuberculosis to be more independent in undergoing pulmonary tuberculosis treatment, active in field counseling activities and using social media as a promotional medium, conducting home visits to patients' homes in an effort to monitor drug compliance in order to increase the acceleration of healing of pulmonary tuberculosis disease which is for their own health and the health of the family around them.